Mengenal Allah Lewat Energi Tidak Dengan Esensi - Pasra Alfrianus Waruwu; Nikolaus Samongantinungglu (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:The energy of God is the radiance of divine love bestowed upon every human being who acts in accordance with what God has spoken and desired. But it cannot be denied that on the part of man there are still some people who are constantly trying to explain the essence of God through ratio and reason, resulting in man doubting his faith in God. But it cannot be denied that on the part of man there are still some people who are constantly trying to explain the essence of God through ratio and reason, resulting in man doubting his faith in God. This study aims to explain that human limitations cannot explain God who is not limited by time and space, but because of His grace God reveals himself to man through incarnation so that man can feel God's love at every moment. In writing this article, the author uses a literature review method that is carried out based on data in the form of Bible studies, journals, and opinions of Church Fathers. The results of this study prove that the knowledge of the true God is only through the word of God who has been incarnated into man.Abstrak:Energi Allah merupakan pancaran kasih ilahi yang di anugerahkan kepada setiap manusia yang bertindak sesuai dengan apa yang difirmankan oleh Allah dan dikehendaki Allah. Namun tidak bisa di pungkiri bahwa di pihak manusia masih terdapat beberapa orang yang terus berusahan menjelaskan esensi Allah melalui rasio dan akal budi, sehingga mengakibatkan manusia ragu akan imannya terhadap Allah. Penelitian ini bertujuan untuk memberi penjelasan bahwa keterbatasan manusia tidak bisa menjelaskan Allah yang tidak dibatasi oleh ruang dan waktu, namun oleh karena anugerah-Nya Allah menyingkapkan diri kepada manusia melalui inkarnasi sehingga manusia bisa merasakan kasih Allah disetiap saat. Dalam penulisan artikel ini penulis menggunakan metode kajian literatur yang dilakukan berdasarkan data berupa telaah Alkitab, jurnal, dan pendapat para Bapa Gereja. Hasil penelitian ini membuktikan bahwa pengenalan Allah yang benar hanya melalui firman Allah yang telah berinkarnasi menjadi manusia.